2022
DOI: 10.9758/cpn.2022.20.4.585
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Fluid Biomarker in Depressive Disorder

Abstract: Major depressive disorders are ranked as the single largest contributor to non-fatal health loss and biomarkers could largely improve our routine clinical activity by predicting disease course and guiding treatment. However there is still a dearth of valid biomarkers in the field of psychiatry. The initial assumption that a single biomarker can capture the myriad of complex processes proved to be naive. The purpose of this paper is to critically review the field and to illustrate the possible practical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Anhedonia is a DA-dependent behaviour and a core feature for depression disorders. In both animal models and depressive patients, the most relevant biological mechanism of anhedonia is the ventral striatal hypoactivation, but dysfunctions in prefrontal cortex also play an important role in abnormal reward processing and impaired reward-related decision making [30]. In addition to changes in behavioural phenotype, our results demonstrated that chronic ACTH injection decreased TH levels in NAcS and ILC.…”
Section: Discussionmentioning
confidence: 71%
“…Anhedonia is a DA-dependent behaviour and a core feature for depression disorders. In both animal models and depressive patients, the most relevant biological mechanism of anhedonia is the ventral striatal hypoactivation, but dysfunctions in prefrontal cortex also play an important role in abnormal reward processing and impaired reward-related decision making [30]. In addition to changes in behavioural phenotype, our results demonstrated that chronic ACTH injection decreased TH levels in NAcS and ILC.…”
Section: Discussionmentioning
confidence: 71%
“…The selected studies were very heterogeneous in their design, settings, subjects, and outcome measures. Thus, we first subdivided them into the following groups: (1) open label clinical trials (Table 1) and ( 2) double-blinded (DB) randomized clinical trials (RCTs) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Depression, a pervasive and debilitating mental health disorder, affects millions of individuals worldwide, contributing to substantial suffering and reduced quality of life [1]. Despite decades of research and therapeutic innovations, conventional treatments such as antidepressant medications and psychotherapy are not universally effective, leaving a significant proportion of individuals with treatment-resistant depression (TRD) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Overall results were positive, however unfortunately this line of research has not been carried on and at present there is not clear evidence of a readily translatable clinical use. However it remains of interest also considering the continuous development in biomarkers discoveries in depression [ 76 ]. An alternative approach is the administration of immunomodulatory interleukins, such as interleukin-2.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%